2018
DOI: 10.1177/1069397118815111
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in the Perception of Personal Growth Among Adolescents

Abstract: Research shows that some adolescents experience positive psychological changes resulting from highly stressful life events. Because “positive change” is a value-laden concept, there may be cross-cultural differences in this conception of growth. The purpose of this study was to qualitatively and quantitatively assess different perceptions of personal growth across cultures. Adolescents from Japan ( n = 288, Mage = 16.16) and the United States ( n = 155, Mage = 16.21) completed demographic information and wrote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The first value of personal growth, that of relationships, is consistent with the experience of an interdependent self (Kitayama et al, 2000). Previous studies on people in other collectivistic cultures also showed conceptualisations of personal growth with strong emphasis on relationships (e.g., Dominick & Taku, 2019). Because Ghanaian Orthodox Christians have strong ties to the collectivistic culture that is indigenous to Ghana, this finding was expected (Hofstede, 2019;Markus & Kitayama, 1991;Meyer, 2004;Omenyo, 2011;Salter & Adams, 2012).…”
Section: The Value Of Relationshipsmentioning
confidence: 56%
See 1 more Smart Citation
“…The first value of personal growth, that of relationships, is consistent with the experience of an interdependent self (Kitayama et al, 2000). Previous studies on people in other collectivistic cultures also showed conceptualisations of personal growth with strong emphasis on relationships (e.g., Dominick & Taku, 2019). Because Ghanaian Orthodox Christians have strong ties to the collectivistic culture that is indigenous to Ghana, this finding was expected (Hofstede, 2019;Markus & Kitayama, 1991;Meyer, 2004;Omenyo, 2011;Salter & Adams, 2012).…”
Section: The Value Of Relationshipsmentioning
confidence: 56%
“…Research has explored conceptualisations of personal growth in the collectivistic cultures of East Asia and Europe (e.g., Dominick & Taku, 2019), but not beyond these regions (Suh & Oishi, 2004). Ghana is a country in Sub-Saharan Africa with a collectivistic culture (15 on the Individualism index; Hofstede Insights, 2019).…”
mentioning
confidence: 99%
“…Research shows that both adolescents and adults experience also positive psychological changes in the face of crises and stressful life experiences, which they define as personal growth (Tedeschi & Calhoun, 1996 ; Kilmer et al, 2014 ). The concept of personal growth can take on different meanings in different cultures, as shown by Dominick and Taku’s research ( 2019 ) among Japanese and American adolescents (aged 13–19). Although there are common characteristics that the youth associate with personal growth, Japanese adolescents associate personal growth more with social connection, while American adolescents associate it with change.…”
Section: Adolescence Religiosity Crisis and Personal Growthmentioning
confidence: 99%
“…Meanwhile, the research of Steele, Elliott, and Phipps [27] demonstrated that Black children display lower levels of anger expressivity and higher levels of anger control compared to White children. The East Asian (Eastern) world tends to be collectivist where each person focuses on the community and group to which they belong, and what is best for everyone over themselves [28]. It leads to a strong support network that assists adolescents convey feelings such as hot-tempered.…”
Section: Hot-temperedness By Gendermentioning
confidence: 99%